Experiences of patients and healthcare professionals of NHS cardiovascular health checks: a qualitative study - Riley, R. (J Public Health (Oxf), 2016)
BACKGROUND: NHS Health Checks are a national cardiovascular risk assessment and management programme in England and Wales. We examined the experiences of patients attending and healthcare professionals (HCPs) conducting NHS Health Checks. METHODS: Interviews were conducted with a purposive sample of 28 patients and 16 HCPs recruited from eight general practices across a range of socio-economic localities. Interviews were audio recorded, transcribed, anonymized and analysed thematically. RESULTS: Patients were motivated to attend an NHS Health Check because of health beliefs, the perceived value of the programme, a family history of cardiovascular and other diseases and expectations of receiving a general health assessment. Some patients reported benefits including reassurance and reinforcement of healthy lifestyles. Others experienced confusion and frustration about how results and advice were communicated, some having a poor understanding of the implications of their results. HCPs raised concerns about the skill set of some staff to competently communicate risk and lifestyle information. CONCLUSIONS: To improve the satisfaction of patients attending and improve facilitation of lifestyle change, HCPs conducting the NHS Health Checks require sufficient training to equip them with appropriate skills and knowledge to deliver the service effectively.